Purificação parcial da bsp5 do plasma seminal bovino - Otávio, Kamila de Sousa (2017)
Seminal plasma has been the subject of several studies due to its importance in sperm physiology, which analysis of reproductive fluids provides crucial information for understanding the mechanisms that determine the fertile ability of male gametes. The objective of the present study was to indicate a method to purify the Binder of SPerm 5 (BSP5), a 30-kDa protein present in the vesicles gland fluid from Bos indicus bulls. The seminal fluid extracted from seminal vesicles glands was obtained in abattoir, and subsequently subjected to heparin affinity chromatography (Hitrap Heparin HP), followed by ion exchange chromatography (SP Sepharose). For the monitoring of purification, SDS-PAGE was performed and western blotting with BSP5-specific antibody was performed for protein confirmation. Based on heparin-binding proteins, it was observed two well-separated peaks (nHBP and HBP), which heparin-binding proteins (HBP) represented a percentage of 51.5% of seminal vesicle fluid proteins. HBPs, when separated by ion exchange chromatography, showed four peaks (P1, P2, P3 and P4), which the peaks of binding proteins (P3 and P4) represented 80.97%. Western blot with anti-BSP5 antibody purified from rabbit antiserum confirmed the presence of the 30-kDa band in seminal vesicle fluid, HBPs and ion exchange peak 4. From this partial purification, it was observed that heparin followed by ion exchange chromatographies are effective to capture the BSP5. However, it is necessary to extend this method, followed by confirmations through sequencing and mass spectrometry. Moreover, from this purification it is possible to perform functional tests that allow the understanding of the mechanism by which BSP proteins modulate the sperm capacitation, in addition to increasing biotechnological processes.